Essential oil composition of Salvia fruticosa Mill. populations from Balkan Peninsula - Ivana Cvetkovikj; Gjoshe Stefkov; Marija Karapandzova; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2015)
The aim of this study was to investigate the yield and chemical composition of the essential oil (EO) isolated from 19 different populations of Salvia fruticosa Mill. (Greek sage, Lamiaceae) from nine different regions of Albania and Greece. The EO yield ranged from 0.25% to 4.00%. Eighteen of the total analyzed populations met the Ph.Eur.8.0 minimal requirements concerning the essential oil yield. Performing GC/FID/MS analyses, a total of 75 components were detected, representing 79.15-97.83% of the oils. Thirteen components (α-pinene, camphene, β-pinene, myrcene, 1,8-cineole, γ-terpinene, cis-thujone, trans-thujone, camphor, terpinene-4-ol, trans-(E)-caryophyllene, aromadendrene and α-humulene) were identified in all samples, with 1,8-cineole as a predominant constituent. Statistical analysis showed that the geographical origin of plants did not have significant influence on the variation in chemical composition of the Greek sage essential oil.